2013
DOI: 10.1021/ja404830y
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins Fused with Strongly Electron-Donating 1,3-Dithiol-2-ylidene Moieties: Redox Control by Metal Cation Complexation and Anion Binding

Abstract: A new class of redox-active free base and metalloporphyrins fused with the 1,3-dithiol-2-ylidene subunits present in tetrathiafulvalene, termed MTTFP (M = H2, Cu, Ni, Zn), have been prepared and characterized. The strong electron-donating properties of MTTFP were probed by electrochemical measurement and demonstrated that oxidation potentials can be tuned by metalation of the free base form, H2TTFP. X-ray crystal structures of H2TTFP, ZnTTFP, and CuTTFP revealed that a severe saddle-shape distortion was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…A wide variety of porphyrins and analogues have been developed and explored as powerful functional tools and as building blocks of supramolecular systems given their tunability, rich coordination chemistry, strong light absorption, and high light emission properties [70][71][72][73][74][75][76][77]. Such features conferred to these molecules a range of biological, photochemical, and photophysical properties with relevant and direct application on diseases' treatment [19,78,79], biological imaging [19,80], and analytical methods [81,82], as well as applications in industrial [83], photocatalytic [84], molecular photovoltaics [85,86], and nonlinear optics (NLO) devices [87].…”
Section: General Aspects Of the Porphyrin Propertiesmentioning
confidence: 99%
“…A wide variety of porphyrins and analogues have been developed and explored as powerful functional tools and as building blocks of supramolecular systems given their tunability, rich coordination chemistry, strong light absorption, and high light emission properties [70][71][72][73][74][75][76][77]. Such features conferred to these molecules a range of biological, photochemical, and photophysical properties with relevant and direct application on diseases' treatment [19,78,79], biological imaging [19,80], and analytical methods [81,82], as well as applications in industrial [83], photocatalytic [84], molecular photovoltaics [85,86], and nonlinear optics (NLO) devices [87].…”
Section: General Aspects Of the Porphyrin Propertiesmentioning
confidence: 99%
“…Asimilar deformation was reported for porphyrin-TTF (TTF = tetrathiafulvalene) conjugates with the quinoidal forms,w hich are also nonaromatic. [29] iii)DFT calculationso fc ompounds 1' and 1' 2 + + :I no rder to clarify the electronic structure of the dicationics pecies, DFT calculations werep erformed for complexes 1' and 1' 2 + . [30] Both compounds 1' and 1' 2 + are of virtually fourfold symmetry and selected bond lengths andapart of the Kohn-Shamo rbitals are shown in Table 1a nd Figure1 1, respectively.T he calculated bond lengths for the RuÀCCÀCm oieties of compounds 1' and 1' 2 + agree wellw ith the bond lengths observed for compound 1 and [1 2 + ](PF 6 ) 2 .F or complex 1',t he HOMO is distributed over the four RuÀCCm oieties and the porphyrin a 2utype orbital, whereas the LUMOs are virtually degenerated and are composed of the porphyrin e gx -type orbitals coupled with some RuÀCCc ontribution.…”
Section: Monocationic Species [1 + ](Pf 6 )mentioning
confidence: 99%
“…[52] The TEA + cation is known to bind effectively to the TTF-C4P cavity, thereby repelling Li [52] Similarly, it has been reported that porphyrins fused with the 1,3-dithiol-2-ylidene subunits present in tetrathiafulvalene (MTTFP) and Li + @C 60 underwent thermal electron transfer through complex formation mediated by anion binding. [56] 60 )* as a strong electron acceptor in photoinduced electron-transfer reactions with various electron donors. [59] The rate constants of electron transfer (k et ) from various electron donors to 3 (Li + @C 60 )* are significantly larger than those to C 60 when the rate constants are less than the diffusion-limited value.…”
Section: Electron-transfer Properties Of LImentioning
confidence: 99%